Stars, Starallüren und Starkult im kaiserzeitlichen Musikbetrieb des Römischen Reiches - Scheithauer, Andrea (Archiv für Musikwissenschaft, 2021)
This paper examines the criteria that shaped the opinions of antique authors regarding eccentric and effusive musicians of Imperial Rome. Aiming to dazzle their audiences with their showmanship, they constantly embellished their extravagant costumes and ingratiated themselves to their fans with capriciousness, vanity, and arrogance. Rivalries with colleagues were characterized by jealousy and envy, while their relationship to audiences was fraught with fear and counterbalanced by paid claques. Due to their extraordinary talent and sex appeal, they were mainly admired and adored by women, which led to veritable personality cults that in turn conditioned the interaction between these musicians and their female fans.
Gesehen am 08.07.2022